2016
DOI: 10.1038/aps.2016.98
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Physcion, a naturally occurring anthraquinone derivative, induces apoptosis and autophagy in human nasopharyngeal carcinoma

Abstract: Aim: Physcion is a major bioactive ingredient in the traditional Chinese medicine Radix et Rhizoma Rhei, which has an anthraquinone chemical structure and exhibits a variety of pharmacological activities including laxative, hepatoprotective, anti-inflammatory, antimicrobial and anti-proliferative effects. In this study we investigated the effect of physcion on human nasopharyngeal carcinoma in vitro and in vivo, as well as the mechanisms underlying the anti-tumor action. Methods: The nasopharyngeal carcinoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…Besides solid tumor, the role of physcion in hematological malignancies has also been established (Liu et al, ). Moreover, physcion‐induced autophagy has been shown to promote cell apoptosis in human nasopharyngeal carcinoma (Pang et al, ). In our previous work, we focused on the neoplastic activities of physcion against HCC and found that physcion could induce the intrinsic apoptotic pathway (Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides solid tumor, the role of physcion in hematological malignancies has also been established (Liu et al, ). Moreover, physcion‐induced autophagy has been shown to promote cell apoptosis in human nasopharyngeal carcinoma (Pang et al, ). In our previous work, we focused on the neoplastic activities of physcion against HCC and found that physcion could induce the intrinsic apoptotic pathway (Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis‐inducing effect of physcion in breast cancer cells, colon cancer cells, cervical carcinoma cells, and nasopharyngeal carcinoma cells has also been documented in a variety of studies (Chen et al, ; Hong et al, ; Pang et al, ; Wijesekara et al, ). Meanwhile, extracellular matrix metalloproteinase inducer (EMMPRIN) (Chen et al, ), 6‐phosphogluconate dehydrogenase (Lin et al, ), and Sp1 (Pang et al, ) have been considered to be molecule targets accounting for the antitumor activity of physcion. Our previous findings have also shown that physcion could inhibit tumor growth and induce apoptosis in HCC (Pan et al, , ).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Pang et al . believe that emodin methyl ether can induce the ROS/miR‐27a/ZBTB10 signaling axis by targeting Sp, and induce apoptosis and autophagy in nasopharyngeal carcinoma cells . Gao et al .…”
Section: Discussionmentioning
confidence: 99%
“…21 Pang et al believe that emodin methyl ether can induce the ROS/miR-27a/ZBTB10 signaling axis by targeting Sp, and induce apoptosis and autophagy in nasopharyngeal carcinoma cells. 22 Gao et al confirmed that overexpression of miR-138-5p enhances the sensitivity of nasopharyngeal carcinoma cells to radiation by targeting EIF4-EBP1. 23 Although the aforementioned studies have explored the relationship between autophagy and apoptosis in nasopharyngeal carcinoma on cancer cell proliferation, tumor growth, and radiotherapy reactivity, the conclusions are still not uniform.…”
Section: Expression Of Related Proteins In Nude Mice Xenograftsmentioning
confidence: 97%